Irrigation management for improving productivity nutrient uptake and water-use efficiency in system of rice intensification: a review - Dass, Anchal; Dhar, Shiva (Annals of Agricultural Research, 2014)
System of rice intensification (SRI) technique is a relatively recent innovation in the rice cultivation. It was developed to enable resource constrained farmers to raise rice production and income without relying on purchased external inputs, which they cannot afford. Recently, this system of rice growing has drawn much attention for its apparent success in increasing productivity of rice fields. With SRI methods, rice yields exceeding 15 t ha-1 have been reported. This method has now spread to more than 60 countries of the world and more than 5 million farmers are using one or the other recommended practice of SRI. Researches with SRI world-over have revealed that high yields from the SRI method are the consequence of improvement in plant environment rather than enhancement of physiological potential of the plant itself. Use of young seedlings, additions of organic manures, wider spacing, and greater aeration from intermittent irrigation have been reported to mediate high yields under SRI. Irrigation at 2-5 days after disappearance of ponded water (DADPW) have been shown to save irrigation water as high as 50% with higher or marginally low yields and higher B:C ratio compared to conventional flooding. Water-use efficiency (WUE) in conventional transplanted rice is only 20-30%. However, SRI could improve WUE by 68-94% and irrigation WUE by 100-130% over traditional flooding. In general, concentration and uptake of N, P, Zn and Cu have been higher under alternate wetting and drying condition while concentration and uptake of K, Fe and Mn have been found to be higher with continuous flooding.